Growth, nutrient uptake and yield of ginger as impacted by potting media, foliar nutrition and microbial inoculants - Sudha, B.; John, J.; Meera, A.V.; Sajeena, A. (Journal of Spices and Aromatic Crops, 2020)
Experiments were conducted during 2017-19 at the Integrated Farming System Research Station, Karamana, Kerala Agricultural University for assessing the impact of quantity of potting media, foliar application of multinutrient mixture IISR Power Mix G and microbial inoculants Arbuscular Mycorrhizal Fungi (AMF) and Trichoderma on the growth, nutrient uptake and yield of ginger variety Karthika grown as pot culture. The study revealed that 12 and 15 kg of potting media filled grow bags could produce comparable yields of ginger significantly higher than that obtained with 9 kg of potting media. Application of IISR Power Mix G @ 0.5% at 2 and 3 months of planting enhanced the yield of ginger to the tune of 11 per cent in comparison to control. Microbial inoculants AMF (5 g plant-1) and Trichoderma (1 kg mixed with 90 kg FYM and 10 kg neem cake and 250 g of the mixture used) applied at planting time followed by Trichoderma at 1 month after planting resulted in higher fresh ginger yield of 596.67 g bag-1 and was comparable to 550 g of fresh ginger obtained with application of AMF and Trichoderma at planting.